Beneficios cognitivos, emocionales y sociales del juego en la edad preescolar. - Carrera Ledezma, Maria Fernanda (2025)
Sensory play represents a fundamental tool for the comprehensive emotional development of preschool-aged children, allowing them to explore and understand the world through multisensory experiences. Despite evidence of its benefits, significant gaps persist in its implementation within educational and family contexts. This study arises from the need to theoretically and contextually analyze the impact of sensory play on children's emotional development, considering that many environments still prioritize academic approaches over socio-emotional development. Methodologically, a literature review was conducted with a qualitative and descriptive-analytical approach, based on updated scientific sources (2018– 2024) obtained from databases such as Scopus, SciELO, Redalyc, and Google Scholar. Analytical techniques such as critical reading and thematic coding were applied, prioritizing studies focused on the relationship between sensory play and emotions in children aged 3 to 6 years. Among the most relevant results, it was identified that sensory play promotes emotional self-regulation, the recognition and expression of feelings, the development of empathy, and socialization. It was also evident that children who participate in guided sensory activities tend to calm down more easily, improve their self-esteem, and establish stronger emotional bonds. The importance of active family and teacher participation in promoting these spaces was also highlighted. In conclusion, it is reaffirmed that sensory play not only stimulates brain plasticity but also acts as a bridge to building a positive self-image and children's emotional well-being. Therefore, there is an urgent call to strengthen its inclusion in educational practices, recognizing play as a vital pedagogical strategy in early childhood.